Biolayer interferometry is insufficiently sensitive for direct measurement of IgM quantity and avidity in Atlantic salmon (Salmo salar) serum. Issue 134 (March 2023) - English, Chloe J.; Li, Angus; Barnes, Andrew C.
Abstract: Quantification of specific antibodies underpins the assessment of adaptive immunity in response to vaccination or infection and is performed by enzyme-linked immunosorbent assay (ELISA). A biolayer interferometry (BLI) assay was recently developed that simultaneously quantifies IgM antibodies and their avidity in giant grouper ( Epinephelus lanceolatus ) sera and proved to be a robust, repeatable and more high-throughput alternative to ELISA [1]. Here we attempted to optimise a similar single-step BLI assay using an Octet HTX instrument to quantify IgM specific to the hapten 2, 4-dinitrophenol (DNP) in serum from Atlantic salmon ( Salmo salar ) primed and boosted with DNP conjugated to keyhole limpet hemocyanin. Highlights: BLI can measure giant grouper antibody quantity and avidity however we could not optimise a new BLI assay to detect IgM in Atlantic salmon. Low IgM concentration in Atlantic salmon and non-specific binding of other serum proteins hindered accurate quantification of DNP-specific IgM. Non-specific binding was eliminated by ammonium sulphate precipitation but this is not a practical option for analysing individual fish samples. Species-specific detection antisera for immunoglobulins remain essential reagents for serum analysis in Atlantic salmon injected with DNP-KLH.